China's Changing Trade Elasticities - Aziz, Jahangir (IMF Working Papers; Working Paper ;, 2007)
China's sectoral trade composition, product quality mix, and import content of processing exports have all changed substantially during the past decade. This has rendered trade elasticities estimated using aggregate data highly unstable, with more recent data pointing to significantly higher demand and price elasticities. Sectoral differences in these parameters are also very wide. All this suggests greater caution in using historical data to simulate the response of the China's economy to external shocks and exchange rate changes. Analyses based on models whose estimated coefficients largely reflect the China of the 1980s and 1990s are likely to turn out to be wrong, perhaps even dramatically.